Synovial Sarcoma of the Spine: A Rare Intradural Extramedullary Tumour - Carvalho, Ajay Sebastian; Yadav, Kishan Kumar; Gupta, Vijay Kumar (Nepal Journal of Neuroscience, 2020)
Synovial sarcoma (SS) accounts for 5- 10% of all adult soft-tissue sarcomas and only 5% arises in the spine. It presents like any other spinal tumor, namely axial pain with symptoms due to neural compression. Imaging findings can also be similar to any other benign spinal tumor.We present a 43-year-old male who presented with symptoms of radiculopathy and neural compression and imaging revealed a dumbbell tumor at C6 to D1 with transforaminal and paraspinal extension on the right side. After surgical excision the histopathology revealed a rare synovial sarcoma of the spine.Synovial sarcoma of the spine though rare, are difficult to differentiate based on their presentation and imaging characteristics from benign spinal tumors. However, subtle findings on imaging and a pre-operative biopsy may aid in performing a more definitive surgery upfront rather than a re-do surgery after the histopathological diagnosis.